A Three-Dimensional User Interface for Neurosurgical Visualization - Goble, John C.; Hinckley, Ken; Kassell, Neal F.; Pausch, Randy (1994)
We describe a 3-D user interface for preoperative neurosurgical planning based on the physical manipulation of familiar real-world objects in free space. Using these passive interface props, neurosurgeons can apply their existing skills to specify spatial relationships in a natural and direct manner. The interface currently employs a head viewing prop, a cutting-plane selection prop, and a trajectory selection prop. Each prop is a simple real-world tool, the position and orientation of which is tracked by the computer. The behaviors associated with each prop serve as 'interaction primitives' which can be composited to describe complex spatial relationships, resulting in a powerful, expressive, and conceptually simpler user interface. From the surgeon's perspective, the interface is analogous to holding a miniature skull which can be 'sliced' and 'pointed to' using the cutting-plane and trajectory props. Our informal evaluation sessions have shown that with a cursory introduction, neurosurgeons who have never seen our interface can understand and use it without training.